PROFIL GLUKOSA DARAH PADA BERBAGAI PARITAS INDUK SA PI PERAH FRIES HOLLAND PASCA PARTUS - Bambang Hadisutanto; . Paggi; Sutarman Muhardja; Siti Darodjah; Bambang Purwantara (Partner, 2009)
Parity gives an indication of physical maturity of cows. Physical maturity state of primiparous was 82 – 90% while that for pluriparous was 100%. In postpartum period, cows have a negative energy balance. Cows experiencing this condition will use the deposit glycogen in their liver and lipids in adipose tissue to be metabolized by liver become glucose. This experiment aimed at studying blood glucose at different parities of post-partum Fries Holland dairy cows. One-way classification design was use to observe 90 heads of post-partum dairy cows (30 heads of cows each in the first, the second and the third parity state. Data were analyze with General Linear Model (GLM) and the significant difference data among blood glucoses of the cows further analyzed with Duncan Multiple Range Test (DMRT). The results of the study showed that there was a significant (P<0.05) difference between blood glucose of the first parity state of cows (51. 57±5. 56 mg/dL) compared to that of the second (45. 57±8.01 mg/dL ) and the third (46.7±8.62 mg/dL ) cows. This was due to cows in the first parity is in growing state than in producing milk and reproduction function. Cows in the second and the third parities are in opposite function. Blood glucose profile at different parities of post-partum Fries Holland dairy cows was in the normal range (35-55 mg/dL). Blood glucose of the first parity of cows was higher (51.57±5.56 mg/dL) compared to that in the second (45.57±8.01 mg/dL) and the third cows (46.7±8.62 mg/dL). Key words: Fries Holland cows, parity, blood glucose